Water control fracturing method based on modified super-sulfur water nano material
By using modified supersulfur water nanomaterials in oil and gas well fracturing transformation, the hydrophobic membrane filling cracks is solved, and the problem that hydrophobic proppants cannot fully fill cracks in the prior art is achieved, and better water control effect and oil well production are improved.
Patent Information
- Application Number
- CN202311385095.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the fracturing transformation process of oil and gas wells containing bottom water layer or upper water layer, existing hydrophobic proppants cannot completely fill the cracks in the fracturing fluid, resulting in poor water barrier performance, small action distance and short effective time.
Modified supersulfur water nanomaterial is used to form a dense hydrophobic film by adding it to the base fracturing fluid, changing the wettability of the rock, forming a water-control barrier, and achieving complete filling of the cracks.
It significantly improves oil permeability and water hindering performance, reduces water production in oil and gas wells, improves oil well production, and has a long-lasting water control effect.
Smart Images

Figure CN119878099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil production engineering methods, and specifically relates to a water-controlled fracturing method based on modified supersulfur water nanomaterials. Background Art
[0002] In the field of oil production engineering, fracturing refers to a method of using hydraulic force to form cracks in oil and gas layers during oil or gas production, also known as hydraulic fracturing.
[0003] Fracturing is to artificially create cracks in the formation to improve the flow environment of oil underground and increase the production of oil wells. It plays an important role in improving the flow conditions at the bottom of the oil well, slowing down the interlayer and improving the production of oil layers. However, if the aquifer and water layer are opened during fracturing, it will cause water production in the oil and gas wells and reduce the production capacity of the oil and gas wells. Therefore, water-controlled fracturing must be carried out during the fracturing of oil and gas wells containing bottom water layers or upper water layers.
[0004] For high-water-content and low-permeability sandstone reservoirs, hydrophobic proppants are currently mainly used for water control fracturing. Super hydrophobic materials are coated on the proppants, which can achieve certain water control and oil increase effects. However, due to the carrying effect of the fracturing fluid, the proppants often cannot completely fill the cracks, resulting in poor water-blocking properties of the hydrophobic proppants, small effective distance, and short effective time. Summary of the invention
[0005] The purpose of the present invention is to provide a water-controlled fracturing method by injecting modified supersulfur water nanomaterials, which has the effect of completely filling cracks and improving oil-permeable and water-blocking properties through the modified supersulfur water nanomaterials.
[0006] The technical solution of the present invention is a water-controlled fracturing method based on modified supersulfur water nanomaterials, which is specifically implemented according to the following steps:
[0007] Step 1, preparing a basic fracturing fluid and adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid;
[0008] Step 2: determine the perforation section length, perforation density and perforation phase in the middle and upper part or top of the reservoir according to the single well oil testing project and perform concentrated perforation to obtain the hole position;
[0009] Step 3: According to the oil test engineering plan, water-controlled fracturing construction is carried out on the hole positions to create artificial fractures in the reservoir to obtain the post-construction formation;
[0010] Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3h to 5h to complete the water-controlled fracturing.
[0011] The present invention is also characterized in that:
[0012] Step 1 is implemented as follows:
[0013] Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, with the preparation temperature being 15° C. to 30° C., to obtain a basic fracturing fluid;
[0014] Step 1.2, dispersing nano carbon dioxide and silicon dioxide in a mass ratio of 5 to 5.3:1 into anhydrous ethanol, stirring at room temperature, heating to above 20°C and adding an acid ester coupling agent for heating and stirring, the heating and stirring time is 10 min to 20 min, and drying and grinding the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial;
[0015] Step 1.3, adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0016] In step 1.2, the stirring temperature at room temperature is 10°C to 20°C, and the stirring time is 30min to 40min.
[0017] In step 1.2, the acid ester coupling agent is 0.5% concentration of isopropyl trititanate.
[0018] Step 1.2: The particle size of the modified super-hydrophobic nanomaterial is 15 nm to 200 nm, and the water contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C.
[0019] The perforating method in step 2 is fire perforating or hydraulic sandblasting perforating.
[0020] In step 3, the water-controlled fracturing construction is carried out according to the designed displacement and designed liquid volume.
[0021] In step 4, the proppant is 20-40 mesh quartz sand or 20-40 mesh ceramsite.
[0022] The beneficial effects of the present invention are as follows: the present invention adds 1.0g / L to 5g / L concentration of modified supersulfur water nanomaterials to the basic fracturing fluid, and after the configured fracturing fluid is injected into the rock pores, it is adsorbed on the wall surface to form a dense hydrophobic film, which changes the wettability of the rock, and the surface of the rock pore channel changes from hydrophilic to hydrophobic; the hydrophobic particles accumulate in the pore throats to form bridges, thereby forming a water control barrier, which can achieve a reduction of more than 30% in the water content of the low-permeability and high-water-saturated oil reservoir after pressure testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the water-controlled fracturing method based on modified supersulfur water nanomaterials of the present invention;
[0024] Figure 2 It is the hydrophobic group of the modified supersulfur water nano material particle in the water control fracturing method of the present invention. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The present invention provides a water-controlled fracturing method based on modified supersulfur water nanomaterials, such as Figure 1 , Figure 2 As shown, the specific implementation steps are as follows:
[0027] Step 1, preparing a basic fracturing fluid and adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid; optimizing the concentration by considering the dispersion stability and hydrophobic effect in the fracturing fluid;
[0028] Step 1.1, 0.3% concentration of hydroxypropyl guar gum and 0.5% concentration of polyacrylamide are added to a liquid preparation tank in sequence, and the preparation temperature is 15° C. to 30° C. to obtain a basic fracturing fluid; hydroxypropyl guar gum is used as a drag reducer, and polyacrylamide is used as a thickener, the main purpose of which is to create cracks and carry modified super-hydrophobic nanomaterials and proppants into the cracks;
[0029] Step 1.2, dispersing nano carbon dioxide and silicon dioxide in a mass ratio of 5 to 5.3:1 into anhydrous ethanol, stirring at room temperature, heating to above 20°C and adding an acid ester coupling agent for heating and stirring, the heating and stirring time is 10 min to 20 min, and drying and grinding the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial;
[0030] The stirring temperature at room temperature is 10°C to 20°C, and the stirring time is 30min to 40min; the acid ester coupling agent is 0.5% isopropyl trititanate; the particle size of the modified super-hydrophobic nanomaterial is 15nm to 200nm, and the water contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C.
[0031] The dispersibility of titanium dioxide in the fracturing fluid is improved by using silicon dioxide for surface inorganic coating, and then the stability of titanium dioxide in the fracturing fluid is improved by treating with an acid ester coupling agent.
[0032] Step 1.3, adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0033] Step 2: Determine the perforation section length, perforation density and perforation phase in accordance with the single well oil testing project in the upper middle or top part of the reservoir and perform concentrated perforation to obtain the hole position; the perforation method is fire perforation or hydraulic sandblasting perforation.
[0034] Step 3: According to the oil test project plan, water-controlled fracturing construction is carried out on the hole positions to create artificial fractures in the reservoir to obtain the post-construction formation; the water-controlled fracturing construction is carried out according to the designed displacement and designed liquid volume.
[0035] Step 4: After injecting the prepared fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3h to 5h to complete the water-controlled fracturing; the proppant is 20-40 mesh quartz sand or 20-40 mesh ceramsite.
[0036] Example 1
[0037] This embodiment provides a water-controlled fracturing method based on modified supersulfur water nanomaterials. In the Hou* well of Ansai Oilfield in the Ordos Basin, the layer length is 9, the permeability is 0.59mD, the oil layer thickness is 11m, and the bottom water is developed. The method is specifically implemented in the following steps:
[0038] Step 1, preparing a basic fracturing fluid and adding 1.0 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid;
[0039] Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, the preparation temperature is 15° C., to obtain a basic fracturing fluid;
[0040] Step 1.2, disperse nano carbon dioxide and silicon dioxide in a mass ratio of 5.3:1 into anhydrous ethanol, stir at room temperature, heat to above 20°C, add an acid ester coupling agent, heat and stir for 10 minutes, dry and grind the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial; the room temperature stirring temperature is 10°C, and the stirring time is 30 minutes; the acid ester coupling agent is 0.5% isopropyl trititanate; the particle size of the modified super-hydrophobic nanomaterial is 60nm, the water phase contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C, and the water droplet contact angle after smearing the core is 54.8°.
[0041] Step 1.3, adding 1.0 g / L of the modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0042] Step 2: Determine the perforation section length, perforation density and perforation phase in the upper middle or top part of the reservoir according to the single well oil test project and perform concentrated perforation to obtain the hole position; the perforation method in this embodiment is fire perforation, the perforation section length is 2 meters, the perforation density is 16 holes / meter, and the perforation phase is 60°.
[0043] Step 3: According to the oil test project plan, water-controlled fracturing is carried out on the hole position to create artificial fractures in the reservoir to obtain the post-construction formation; the water-controlled fracturing is carried out according to the designed displacement and designed liquid volume; the designed displacement in this embodiment is 2.2m 3 / min, the designed liquid volume is 270m 3 .
[0044] Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3 hours to complete the water-controlled fracturing; the proppant in this embodiment is 40-mesh quartz sand.
[0045] This embodiment tests the modified super-hydrophobic nano-particle material with a concentration of 1.0g / L and a particle size of 60nm, sets up 5 groups of water phase breakthrough pressure tests, selects cores numbered 2, 6, 17, 31, and 33, and sets the normal pressure group and back pressure group for comparison according to the target formation pressure of 14MPa; sets the bound water group and residual oil group for comparison according to different oil-water ratios. As shown in Table 1, the core injected with 60nm super-hydrophobic particles is used for the scour resistance test. When the displacement reaches about 28PV, the pressure begins to remain stable and still does not drop at 40PV. The experimental results show that the water phase plugging rate of the modified super-hydrophobic nanoparticles reaches more than 68%.
[0046] Table 1
[0047]
[0048] Example 2
[0049] This embodiment provides a water-controlled fracturing method based on modified supersulfur water nanomaterials, which is carried out in the Ji* well of Jiyuan Oilfield in the Ordos Basin, with a layer length of 4+5, a permeability of 0.62mD, an oil layer thickness of 12.3m, oil and water in the same layer, and a water saturation of 72%. The method is specifically implemented in the following steps:
[0050] Step 1, preparing a basic fracturing fluid and adding 1.5 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid;
[0051] Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, the preparation temperature is 20° C., to obtain a basic fracturing fluid;
[0052] Step 1.2, disperse nano carbon dioxide and silicon dioxide in a mass ratio of 5.3:1 into anhydrous ethanol, stir at room temperature, heat to above 20°C, add an acid ester coupling agent, heat and stir for 15 minutes, dry and grind the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial; the room temperature stirring temperature is 15°C, and the stirring time is 35 minutes; the acid ester coupling agent is 0.5% isopropyl trititanate; the particle size of the modified super-hydrophobic nanomaterial is 30nm, the water phase contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C, and the water droplet contact angle after smearing the core is 58.1°.
[0053] Step 1.3, adding 1.5 g / L of the modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0054] Step 2: Determine the perforation section length, perforation density and perforation phase in the upper middle or top part of the reservoir according to the single well oil test project and perform concentrated perforation to obtain the hole position; the perforation method of this embodiment is fire perforation, the perforation section length is 1.5 meters, the perforation density is 16 holes / meter, and the perforation phase is 60°.
[0055] Step 3: According to the oil test project plan, water-controlled fracturing is carried out on the hole position to create artificial fractures in the reservoir to obtain the post-construction formation; the water-controlled fracturing is carried out according to the designed displacement and designed liquid volume; the designed displacement in this embodiment is 2.0m 3 / min, the designed liquid volume is 200m 3 .
[0056] Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 5 hours to complete the water-controlled fracturing; the proppant in this embodiment is 20-mesh ceramsite.
[0057] This embodiment tests the modified super-hydrophobic nano-particle material with a concentration of 1.5g / L and a particle size of 30nm, sets 5 groups of water phase breakthrough pressure tests, selects cores numbered 3, 4, 5, 10, and 32, and sets normal pressure group and back pressure group controls according to the target formation pressure of 18MPa; sets bound water group and residual oil group controls according to different oil-water ratios, as shown in Table 2, and the experimental results show that the water phase plugging rate of the modified super-hydrophobic nano-particles reaches more than 70%. The core injected with 30nm super-hydrophobic particles is used for the scour resistance test. When the displacement reaches about 30PV, the pressure begins to remain stable and does not drop at 45PV.
[0058] Table 2
[0059]
[0060] Example 3
[0061] This embodiment provides a water-controlled fracturing method based on modified supersulfur water nanomaterials, which is carried out in a high-level well in Ansai Oilfield, Ordos Basin, with a layer length of 2, a permeability of 0.91mD, an oil layer thickness of 8.3m, bottom water development, and a water saturation of 67.1%. The method is specifically implemented in the following steps:
[0062] Step 1, preparing a basic fracturing fluid and adding 3.5 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid;
[0063] Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, the preparation temperature is 30° C., to obtain a basic fracturing fluid;
[0064] Step 1.2, disperse nano carbon dioxide and silicon dioxide with a mass ratio of 5.3:1 into anhydrous ethanol, stir at room temperature, heat to above 20°C, add an acid ester coupling agent, heat and stir for 20 minutes, dry and grind the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial; the room temperature stirring temperature is 20°C, and the stirring time is 40 minutes; the acid ester coupling agent is 0.5% isopropyl trititanate; the particle size of the modified super-hydrophobic nanomaterial is 50nm, the water phase contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C, and the water droplet contact angle after smearing the core is 62°.
[0065] Step 1.3, adding 3.5 g / L of modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0066] Step 2: Determine the perforation section length, perforation density and perforation phase in the upper middle or top part of the reservoir according to the single well oil test project and perform concentrated perforation to obtain the hole position; the perforation method of this embodiment is fire perforation, the perforation section length is 1.5 meters, the perforation density is 16 holes / meter, and the perforation phase is 60°.
[0067] Step 3: According to the oil test project plan, water-controlled fracturing is carried out on the hole position to create artificial fractures in the reservoir to obtain the post-construction formation; the water-controlled fracturing is carried out according to the designed displacement and designed liquid volume; the designed displacement in this embodiment is 2.0m 3 / min, the designed liquid volume is 200m 3 .
[0068] Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3 hours to complete the water-controlled fracturing; the proppant in this embodiment is 20-mesh ceramsite.
[0069] This embodiment tests the modified super-hydrophobic nano-particle material with a concentration of 3.5g / L and a particle size of 50nm, sets 4 groups of water phase breakthrough pressure tests, selects cores numbered 7, 8, 9, and 18, and sets a normal pressure group and a back pressure group control according to the target formation pressure of 12MPa; as shown in Table 3, according to different oil-water ratios, a bound water group and a residual oil group control are set. The experimental results show that the water phase plugging rate of the modified super-hydrophobic nano-particles reaches more than 75%. The core injected with 50nm super-hydrophobic particles is used for the scour resistance test. When the displacement reaches about 27PV, the pressure begins to remain stable and does not drop at 42PV.
[0070] Table 3
[0071]
[0072] Example 4
[0073] This embodiment provides a water-controlled fracturing method based on modified supersulfur water nanomaterials, which is carried out in Luo* Well, Huanjiang Oilfield, Ordos Basin, with a layer length of 3, a permeability of 0.83mD, an oil layer thickness of 12.6m, oil and water in the same layer, and a water saturation of 77%. The method is specifically implemented in the following steps:
[0074] Step 1, preparing a basic fracturing fluid and adding 5.0 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid;
[0075] Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, the preparation temperature is 30° C., to obtain a basic fracturing fluid;
[0076] Step 1.2, disperse nano carbon dioxide and silicon dioxide with a mass ratio of 5.3:1 into anhydrous ethanol, stir at room temperature, heat to above 20°C, add an acid ester coupling agent and heat and stir for 20 minutes, dry and grind the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial; the room temperature stirring temperature is 20°C, and the stirring time is 40 minutes; the acid ester coupling agent is 0.5% isopropyl trititanate; the particle size of the modified super-hydrophobic nanomaterial is 40nm, the water phase contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C, and the water droplet contact angle after smearing the core is 62°.
[0077] Step 1.3, adding 5.0 g / L of the modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
[0078] Step 2: Determine the perforation section length, perforation density and perforation phase in the upper middle or top part of the reservoir according to the single well oil test project and perform concentrated perforation to obtain the hole position; the perforation method of this embodiment is fire perforation, the perforation section length is 3.0 meters, the perforation density is 16 holes / meter, and the perforation phase is 60°.
[0079] Step 3: According to the oil test project plan, water-controlled fracturing is carried out on the hole position to create artificial fractures in the reservoir to obtain the post-construction formation; the water-controlled fracturing is carried out according to the designed displacement and designed liquid volume; the designed displacement in this embodiment is 2.4m 3 / min, the designed liquid volume is 155m 3 .
[0080] Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3 hours to complete the water-controlled fracturing; the proppant in this embodiment is 40-mesh ceramsite.
[0081] This embodiment tests the modified super-hydrophobic nano-particle material with a concentration of 5.0g / L and a particle size of 40nm, sets 4 groups of water phase breakthrough pressure tests, selects cores numbered 7, 8, 9, and 18, and sets a normal pressure group and a back pressure group control according to the target formation pressure of 12MPa; as shown in Table 4, according to different oil-water ratios, a bound water group and a residual oil group control are set, and the experimental results show that the water phase plugging rate of the modified super-hydrophobic nano-particles reaches more than 75%. The core injected with 50nm super-hydrophobic particles is used for the scour resistance test. When the displacement reaches about 27PV, the pressure begins to remain stable and does not drop at 42PV.
[0082] Table 4
[0083]
Claims
1. A water-controlled fracturing method based on modified supersulfur water nanomaterials, characterized in that: Follow the steps below to implement it: Step 1, preparing a basic fracturing fluid and adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial to obtain a configured fracturing fluid; Step 2: determine the perforation section length, perforation density and perforation phase in the middle and upper part or top of the reservoir according to the single well oil testing project and perform concentrated perforation to obtain the hole position; Step 3: Perform water-controlled fracturing construction on the hole positions according to the oil testing engineering plan to create artificial fractures in the reservoir to obtain a post-construction formation; Step 4: After injecting the configured fracturing fluid carrying the proppant into the constructed formation, shut down the well for 3h to 5h to complete the water-controlled fracturing.
2. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 1, characterized in that: The step 1 is specifically implemented according to the following steps: Step 1.1, adding 0.3% hydroxypropyl guar gum and 0.5% polyacrylamide into a liquid preparation tank in sequence, with the preparation temperature being 15° C. to 30° C., to obtain a basic fracturing fluid; Step 1.2, dispersing nano carbon dioxide and silicon dioxide in a mass ratio of 5 to 5.3:1 into anhydrous ethanol, stirring at room temperature, heating to above 20°C and adding an acid ester coupling agent for heating and stirring, wherein the heating and stirring time is 10 to 20 minutes, and drying and grinding the obtained solid-liquid mixture to obtain a modified super-hydrophobic nanomaterial; Step 1.3, adding 1.0 g / L to 5 g / L of modified supersulfur water nanomaterial into the basic fracturing fluid and stirring for not less than 30 minutes to obtain the configured fracturing fluid.
3. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 2, characterized in that: The normal temperature stirring temperature in step 1.2 is 10° C. to 20° C., and the stirring time is 30 min to 40 min.
4. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 2, characterized in that: The acid ester coupling agent in step 1.2 is 0.5% concentration of isopropyl trititanate.
5. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 2, characterized in that: The particle size of the modified super-hydrophobic nanomaterial in step 1.2 is 15 nm to 200 nm, and the water contact angle of the modified super-hydrophobic nanomaterial is not less than 100°C.
6. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 1, characterized in that: The perforating method in step 2 is fire perforating or hydraulic sandblasting perforating.
7. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 1, characterized in that: The water-controlled fracturing construction in step 3 is carried out according to the designed displacement and designed liquid volume.
8. The water-controlled fracturing method based on modified supersulfur water nanomaterials according to claim 1, characterized in that: The proppant in step 4 is 20-40 mesh quartz sand or 20-40 mesh ceramsite.
Citation Information
Patent Citations
Water-control effect-enhancing fracturing method of carbonate reservoir
CN105089594A
Preparation method of propping agent coated with superhydrophobic polymeric membrane
CN106147744A
Super-hydrophobic and anti-icing transparent coating and preparation method thereof
CN106634267A
Water-swelling nano material and water control and oil increment fracturing method based on same
CN107418552A
Water control fracturing stimulation method for oil and gas well
CN111022020A
Cited By
Oil-permeable and water-blocking coated quartz sand for fracturing and preparation method of oil-permeable and water-blocking coated quartz sand
CN121064827A
Oil permeable and water blocking film coated quartz sand for fracturing and preparation method thereof
CN121064827B